The Impact of Nurse-Led Initiatives on Patient Satisfaction: A Systemic Review - Takroni, Wedyan Abduallh; Alsubyani, Walaa Abdulwahab; Hadidi, Bayan Yehia Abdo; Qohal, Aisha Hamza; Almudyir, Eyad Mohammmed; Alhawbani, Ahmed Jabril (Journal of Posthumanism, 2024)
Nursing interventions include many actions such as physical care, emotional support, patient education, prescription delivery, and coordination of healthcare services. They significantly influence patient outcomes. This study sought to determine the most efficacious nursing strategies for enhancing patient outcomes. A comprehensive evaluation was performed to evaluate the effect of nursing interventions on patient outcomes in diverse healthcare environments. Six studies were incorporated for the review. A thorough search was conducted utilizing databases including the Cochrane Library, Google Scholar, Web of Science Core Collection, PubMed, and Scopus. Only papers published in English from January 2000 to December 2024 were included. A systematic procedure was implemented, encompassing study selection, data extraction, and synthesis of findings. The findings from these studies illustrate the beneficial effects of particular nursing treatments across diverse healthcare environments. The analysis of the chosen trials demonstrated that nursing interventions significantly enhanced patient outcomes. Interventions include patient education, medication management, infection control, pain management, wound care management, and fall prevention demonstrated efficacy across various healthcare environments. This review's findings illustrate the beneficial effects of several nursing interventions across diverse healthcare environments. Implementing these treatments can enhance patient outcomes, improve patient safety, and contribute to superior overall healthcare quality.